Multidisciplinary management of a patient with van der Woude syndrome: A case report - Tehranchi, Azita (Int J Surg Case Rep, 2016)
INTRODUCTION: Van der Woude syndrome (VWS) is the most frequent form of syndromic cleft lip and palate (SCLP) accounting for 2% of all patients with CLP. CASE PRESENTATION: We describe the orthodontic treatment of a girl diagnosed with VWS referred by her family dentist for her cosmetic concerns. DISCUSSION: Comprehensive orthodontic treatment, secondary bone graft, distraction osteogenesis (for a deficient maxilla), secondary palatoplasty and excision of lower lip pits, as well as orthodontic and prosthetic procedures may provide a satisfactory outcome. Genetic testing showed a known putative splice site mutation (c.174 + 1 G/A) as the prime cause of VWS in our patient and her family. CONCLUSION: SCLP has significant effects on facial aesthetics and the psychosocial status. Parents should be assessed and counseled appropriately. This condition is treatable in the absence of life threatening systemic anomalies. An interdisciplinary team approach is advocated.